Mashrū’ Taf’īl al-Khiṭāb al-Salafī Fī al-Majāl al-Balāghī: Min Naqd al-Adlajah Ilā al-Naqd al-Mu`adlaj: [The Project of Salafi Discourse Activism in Rhetorical Context: From Critics of Ideologization into Ideological Criticism] - Muhdhor, Ahmad; Masrukhin, Mohammad Yunus; Abdullah, M. Amin (UIN Sunan Kalijaga Yogyakarta, 2022)
The rhetorical project of Muhammad al-Ṣāmil, which called Balāghat Ahl al-Sunnah comes in the field of purifying Islamic knowledge from extraneous impurities and deviations. We discuss the foundations of this project and its cognitive practices as a discourse that can be analyzed according to approaches to discourse analysis, especially Foucault and Fairclough approaches, to arrive at a critical evaluation of the issue and its consequences. In the end, we reached the following results: First, the project is merely a transfer of “subjectivity” from the subjectivity of the theologians (mutakallimīn) to the subjectivity of those who reject the theological thought (‘ilm al-kalām); Secondly, the project is, in fact, a rhetorical practice through which authoritarian practices are carried out to exclude others and deconstruct their authority. Third, the support of the official educational institution for the project suggests ideological support as a policy by the state institution that funds it, and this means directing the knowledge path in a politically and ideologically biased direction. In sum, it is said that the project started with an ideology critique and ended with ideologized critique.